Analyzing the Act of a Literary Hero with “Finite Information Flow” Model - Shvetsova, Tatyana V.; Zemlyanikin, Anton P. (Journal of History Culture and Art Research, 2019)
The article discusses the problem of the "act of a literary hero" in the historical and literary process. It is shown on the example of the category “act of a literary hero” that the idea of a literary hero and his act underwent changes in various historical and literary periods. Such changes were the result of the crisis processes that accompanied the transformation in the picture of the world. It is necessary to identify key aspects that allow us to talk about a change in the literary paradigm, which includes ideas about the literary hero and his deed. The “finite information flow” model was used for this; it is an instrument of categorical-systemic methodology. Thus, the reasons for changing ideas about the act of a literary hero are revealed. These reasons include the design of individual phases of the historical and literary process; changing the picture of the world; the formation of the novel genre, the subject of the image of which is the alienation between the hero and the world. The expediency of using the “finite information flow” model in literary criticism is proved.